The Implications of Strengthening the Pancasila Student Profile and the Rahmatan Lil Alamin Student Profile for Students’ Spiritual Intelligence - Bungawati Bungawati; Amrul Aysar Ahsan; Nur Hikmah; Putri Nasrahim (STAI Publisistik Thawalib Jakarta, 2026)
This research aims to analyze the implications of the Pancasila Student Profile and Rahmatan Lil Alamin Student Profile strengthening project on spiritual intelligence. This type of research uses qualitative descriptive research. The research will be carried out at MAN Palopo which is located on Jalan Ratulangi, Palopo City. The research subjects were MAN Palopo teachers and students. The data collected is qualitative data. The data collection techniques used were observation, interviews and documentation. The instruments used were observation sheets and interview guidelines. The data obtained was then analyzed qualitatively which included three stages, namely data reduction, data presentation and drawing conclusions. The implications of the Project for Strengthening the Pancasila Student Profile and the Rahmatan Lil Alamin Student Profile on students' spiritual intelligence are increasing spiritual activity practices, strengthening students' spiritual awareness, being able to reflect on themselves and internalize spiritual values. Recommendations for further integrating the values ??of the Pancasila Student Profile and the Rahmatan Lil Alamin Student Profile into the learning curriculum in schools.The research problem is how the implementation of P5PPRA affects students’ spiritual intelligence improvement at Madrasah Aliyah Negeri Palopo from a qualitative perspective. The objective of this study is to analyze the implications of the P5PPRA program for students’ spiritual intelligence development at Madrasah Aliyah Negeri Palopo, using a qualitative descriptive design. This study uses a descriptive qualitative approach at Madrasah Aliyah Negeri Palopo involving teachers and students, with data collected through observation, interviews, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing. The findings show that implementing P5PPRA at Madrasah Aliyah Negeri Palopo has a positive impact on students’ spiritual intelligence development by encouraging worship activities, strengthening spiritual awareness, and fostering self-reflection. Students can internalize the values of Pancasila and Rahmatan Lil Alamin in daily life, while teachers serve as facilitators and role models. Project-based learning also enriches meaningful learning experiences, and the integration of spiritual values in the Merdeka Curriculum helps shape students who are more religious, reflective, and responsible in a consistent and sustainable manner. In conclusion, P5PPRA improves students’ spiritual intelligence through worship, reflection, value internalization, and the effective and sustainable role of teachers as mentors. This research is important as a basis for developing P5PPRA-based spiritual learning strategies to strengthen students’ character in a sustainable, context-specific way.